The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10578-011-0242-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive Illusions in Adolescents: The Relationship Between Academic Self-Enhancement and Depressive Symptomatology

Abstract: Positive illusions are systematically inflated self-perceptions of competence, and are frequently seen in areas of great difficulty. Although these illusions have been extensively documented in children and adults, the developmental trajectory remains unclear. This study investigated the relationship between positive illusions and depressive symptomatology and school stress in a sample of 78 typically developing adolescents. Adolescents who were achieving slightly below average in math significantly overestima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…In cases in which one wants to interpret effects of SE in terms of specific ability levels, for example, the data must be assessed on appropriate scales. Ongoing efforts in the literature have already provided us with valid and sophisticated approaches for assessing commensurable self-perceptions and criterion scores for a wide range of different domains (e.g., see Anderson et al, 2012; Gramzow et al, 2008; John & Robins, 1994; Kurt & Paulhus, 2008; Moore & Healy, 2008; Noble et al, 2011; Polzer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases in which one wants to interpret effects of SE in terms of specific ability levels, for example, the data must be assessed on appropriate scales. Ongoing efforts in the literature have already provided us with valid and sophisticated approaches for assessing commensurable self-perceptions and criterion scores for a wide range of different domains (e.g., see Anderson et al, 2012; Gramzow et al, 2008; John & Robins, 1994; Kurt & Paulhus, 2008; Moore & Healy, 2008; Noble et al, 2011; Polzer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For the research question that we address in this manuscript, it is not the average amount of SE that is of interest, but rather its variability across individuals. It was consistently found that individuals differ in the extent to which they self-enhance (e.g., Leising et al, 2016; Noble, Heath, & Toste, 2011; Polzer et al, 1997). Given this finding, a question that arises as a next logical step concerns associations between SE and potential outcome variables: Are individual differences in SE systematically related to individual differences in psychological adjustment, for example?…”
Section: Confounding Effects Of Self-enhancement With Effects Of the ...mentioning
confidence: 99%
“…To what extent is academic self-enhancement adaptive? Some research indicates that viewing one’s academic abilities favorably is beneficial, with findings showing that academic self-enhancement is associated with achieving better grades (Dufner et al, 2012; Gramzow et al, 2014), better psychological adjustment (Dufner et al, 2012; Dufner, Reitz, & Zander, 2014; Kurman & Eshel, 1998; Noble, Heath, & Toste, 2011), and greater motivation to academically succeed (Gramzow et al, 2014; Gramzow & Willard, 2006). Other research suggests that academic self-enhancement is costly, finding that academic self-enhancement is associated with lower grades (Gramzow, Elliot, Asher, & McGregor, 2003) and disengagement from academics (Robins & Beer, 2001).…”
Section: Adaptive and Maladaptive Correlates Of Academic Self-enhancementioning
confidence: 99%
“…When it comes to comparing self-perceptions to reality, we define self-enhancement (SE) as the directed discrepancy between a person's self-view and reality with regard to a specific characteristic of interest (e.g., intelligence). This definition is one of the most commonly applied conceptualizations of SE and is, for example, reflected in the general use of discrepancy measures (e.g., algebraic differences or residual scores) to assess individuals' SE (e.g., see Anderson, Brion, Moore, & Kennedy, 2012;Chung, Schriber, & Robins, 2016;Colvin et al, 1995;Dufner, Reitz, & Zander, 2015;Gabriel, Critelli, & Ee, 1994;Gramzow, Elliot, Asher, & McGregor, 2003;John & Robins, 1994;Kurman & Sriram, 1997;Noble, Heath, & Toste, 2011;Robins & Beer, 2001;Willard & Gramzow, 2009). Note that the term "self-enhancement" (or related terms such as "positive illusion") has sometimes been used to refer to only positive discrepancies between self-views and reality, whereas negative discrepancies have been treated under the label "self-effacement."…”
Section: Definitions Of the Relevant Constructsmentioning
confidence: 99%